EARLY WARNING SYSTEM OF BANKRUPTCY OF INDONESIAN BUSINESS-TO-CONSUMER (B2C) RETAIL Amidst MACROECONOMIC PRESSURE - Murviana Koto (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
Corporate bankruptcy is generally preceded by a decline in financial performance that can be detected early through financial ratio analysis. Entering 2026, the business-to-consumer (B2C) retail sector in Indonesia faces new macroeconomic pressures in the form of a weakening rupiah and contracting retail sales, making early detection of bankruptcy risk crucial for investors and fund managers. This study evaluates the financial health of B2C retail companies listed on the Indonesia Stock Exchange using the Altman Z-Score model as an early warning system instrument, based on signaling theory and agency theory. A quantitative descriptive method was used with a sample of 15 pure B2C retail companies (60 annual financial report observations) for the 2021–2024 period, purposively selected from a population of 31 companies based on the completeness of audited reports and the purity of their B2C business models. The results show that the proportion of companies in the Safe Zone increased from 60.0 percent (2021) to 80.0 percent (2022 and 2024), reflecting a sharp post-pandemic recovery. However, two issuers were found to be consistently in the Distress Zone, indicating structural issues that make them vulnerable to further macroeconomic shocks. This study confirms that the Altman Z-Score is effective as an early warning tool to help investors and fund managers mitigate investment risks in the B2C retail sector amid increasing macroeconomic uncertainty.